Mendialogkan Alquran dengan Pembacanya: Studi Atas Living Qur?an di Periode Klasik dan Pertengahan - H. Zuhri (Institut Agama Islam Negeri (IAIN) Curup, 2019)
The discourse on the Qur'an, until now, is still dominated by the dimensions of the internality of the Qur'an rather than its external dimension. Such conditions create the gap between the Qur'an on one hand and the readers or users of the Qur'an on the other. With using some cases of creating external Quranic dialouging as the core of analysis, this paper will answer the question how to re-readsome classical ideas or concepts in Islamic teaching and studies, especially those relating to the Qur'an, which actually shows the development of discourse for the context of the externalities of the Qur'an in the form of vertical dialogue between readers of al-Quran and the Qur'an itself. Although the existing discourse is still stay in the theological nuances and human interaction with the God, but the discourse has the potential to be further developed to enrich the tradition of Quranic studies. At the same time, in the perspective of the classical living al-Qur'an, it shows that the dialogue of Qur'an in the context of its externality means to dialogue the Qur'an in the context of humanity. Although it can not be separated from the divine dimension, the Qur'an becomes more alive in society and its humanity in the form of dialoging Quran with its readers and humankind generally